2015
DOI: 10.1186/s12882-015-0174-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of cinacalcet use and biochemical control in hemodialysis patients: a retrospective New-user cohort design

Abstract: BackgroundCinacalcet is used to treat secondary hyperparathyroidism among hemodialysis patients. Large-scale epidemiologic studies describing patterns of cinacalcet use, effects on parathyroid hormone (PTH), calcium, and phosphorous levels, and predictors of discontinuation have not been previously reported.MethodsThis retrospective cohort study used a clinical database of a large U.S. dialysis provider (2007–2010) merged with administrative data from the United States Renal Data System. Among new users of cin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
1
15
1
Order By: Relevance
“…Vitamin D can also lead to increased levels of serum calcium and serum phosphate The major limitations of cinacalcet use include GI effects, hypocalcemia, 18,39,52 and high discontinuation rates. [62][63][64][65] The most common adverse events for etelcalcetide include GI effects, diarrhea, and asymptomatic or symptomatic hypocalcemia. 66…”
Section: Beto Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D can also lead to increased levels of serum calcium and serum phosphate The major limitations of cinacalcet use include GI effects, hypocalcemia, 18,39,52 and high discontinuation rates. [62][63][64][65] The most common adverse events for etelcalcetide include GI effects, diarrhea, and asymptomatic or symptomatic hypocalcemia. 66…”
Section: Beto Et Almentioning
confidence: 99%
“…and diet are self-administered and, thus, more challenging to accurately track. With regard to the calcimimetics, a number of studies have shown a high rate of discontinuation with cinacalcet, [62][63][64][65] In a 2010 study, 90 50% of nurses, 42% of dietitians, and 36% of social workers reported that they were ''tired'' or ''extremely tired'' of having to manage medication adherence in hemodialysis patients, as they were spending 13.8 hours each week addressing issues related to patient adherence to medications. Although strategies can be used to address adherence issues (high pill burden, forgetfulness, and frequent changes in medication schedule and dose), 91 nonadherence often leads to failure to achieve clinical targets for PTH, calcium, and phosphate.…”
Section: Beto Et Almentioning
confidence: 99%
“…Therefore, there was a statistically signif-morbidity and mortality in patients with secondary hyperparathyroidism due to dialysis. The available options for treatment of bone mineral disorders do not always provide adequate control of PTH, calcium and phosphorus levels, and are often associated with mismatch and high incidence of discontinuation (2)(3)(4)(5).…”
Section: Resultsmentioning
confidence: 99%
“…We modelled discontinuation with a parametric Weibull function (see electronic supplementary material). For the base case, we used the United States (US) real world data [ 21 ]. To test the sensitivity of the model to persistence assumptions, we applied EVOLVE trial persistence as an upper bound, and the lowest observed real-world persistence in Europe as a lower bound (one-year persistence: EVOLVE 73%, US 27%, France 27%, Germany 22%, Italy 16%).…”
Section: Methodsmentioning
confidence: 99%